Employee perception on the spatial qualities of open plan design in interior designer’s office / Siti Hanisah Mohd Yusoff - Mohd Yusoff, Siti Hanisah (2021)
The aim of this research is to identify the element of spatial qualities in open plan design for interior designer office that are vital for office plan design. The main objectives of this study are to identify user perception towards spatial qualities of open plan design in interior design office and to investigate the element in spatial qualities for open plan design in interior design office. This research was carried out at interior design office in Selangor and the respondent are the employee of the office. The research used a questionnaire to gain data about employee perception and feedback about spatial qualities in their office. A further study, enable researcher to identify employee perception about the spatial qualities in an open plan design office.